National fisheries restricted areas: an alternative tool for the sustainable management of Black Sea vulnerable and economically important fish populations - Niță, Victor; Nenciu, Magda; Begun, Tatiana; Teacă, Adrian; Galațchi, Mădălina; Danilov, Cristian (Frontiers in Marine Science, 2025)
Fisheries Restricted Areas (FRAs), as area-based fisheries management tools, can be effective in providing protection for fisheries and biodiversity, in addition to traditional Marine Protected Areas (MPAs), and are already in effect in waters above 1,000 m of the Mediterranean and the Black Seas. Whereas in the North-Western part of the Black Sea all fishing activities are concentrated in the shallow area (at depths of maximum 90 m), where species and habitats of conservation interest are present, this restriction is completely irrelevant. In this context, given that a FRA can also be established nationally (nFRA), the main objective of this research was pre-identifying suitable area(s) at the Romanian coast and providing the scientific substantiation for such an endeavor. In addition to being a traditional fishing ground for small-scale local fishermen, the study perimeter, which includes the Northern Romanian coast (part of the Marine Zone of the Danube Delta Biosphere Reserve), was chosen for various reasons. First, because of the uniqueness of the habitats found here, it serves as a vital forage area for fish species that are valuable both from a conservation and economic standpoint. Additionally, during the past ten years, beam trawl fishing for the gastropod Rapana venosa (Valenciennes, 1846) has affected the area, potentially causing harm to benthic habitats. A variety of data sources were integrated as part of the research strategy, including the composition and spatial distribution of macrozoobenthos, an inventory of the local fish fauna conducted through scientific fishing (both for commercial fish and species of conservation interest), fish stomach content analysis (by dissection or gastric lavage), and records of fishing effort and catch. The identified Sf. Gheorghe - Sahalin nFRA, covering 272.76 km2 between the 40 m and 50 isobaths, proved to be appropriate according to both ecological and fisheries criteria, and, after public consultation, was established by law, thus becoming the first national Fisheries Restricted Area in the Black Sea, to the benefit of both nature conservation, by spillover effects to adjacent areas, and the livelihood of local coastal communities.